2006
DOI: 10.1016/j.febslet.2006.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Zaprinast, a well‐known cyclic guanosine monophosphate‐specific phosphodiesterase inhibitor, is an agonist for GPR35

Abstract: We found that zaprinast, a well-known cyclic guanosine monophosphate-specific phosphodiesterase inhibitor, acted as an agonist for a G protein-coupled receptor, GPR35. In our intracellular calcium mobilization assay, zaprinast activated rat GPR35 strongly (geometric mean EC 50 value of 16 nM), whereas it activated human GPR35 moderately (geometric mean EC 50 value of 840 nM). We also demonstrated that GPR35 acted as a Ga i/o -and Ga 16 -coupled receptor for zaprinast when heterologously expressed in human embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
154
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(159 citation statements)
references
References 19 publications
5
154
0
Order By: Relevance
“…Moreover, a number of other agonist ligands with antiasthma/antiallergenic pharmacology, including doxantrazole and pemirolast, although lacking a carboxyl function, clearly contain an acid bioisostere related to the triazole structure present in the standard GPR35 surrogate agonist zaprinast. These ligands, although also active at GPR35, displayed marked differences in potency between the rat and human orthologs, a feature previously noted for zaprinast (Taniguchi et al, 2006;Jenkins et al, 2010). The published literature indicates that certain GPR35 agonists such as pamoate (Jenkins et al, 2010), 4-{(Z)-[(2Z)-2-(2-fluorobenzylidene)-4-oxo-1,3-thiazolidin-5-ylidene]methyl}benzoic acid , and various 8-benzamidochromen-4-one-2-carboxylic acids (Funke et al, 2013) are highly selective for the human ortholog, whereas others such as pemirolast and amlexanox are highly selective for the rat ortholog.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Moreover, a number of other agonist ligands with antiasthma/antiallergenic pharmacology, including doxantrazole and pemirolast, although lacking a carboxyl function, clearly contain an acid bioisostere related to the triazole structure present in the standard GPR35 surrogate agonist zaprinast. These ligands, although also active at GPR35, displayed marked differences in potency between the rat and human orthologs, a feature previously noted for zaprinast (Taniguchi et al, 2006;Jenkins et al, 2010). The published literature indicates that certain GPR35 agonists such as pamoate (Jenkins et al, 2010), 4-{(Z)-[(2Z)-2-(2-fluorobenzylidene)-4-oxo-1,3-thiazolidin-5-ylidene]methyl}benzoic acid , and various 8-benzamidochromen-4-one-2-carboxylic acids (Funke et al, 2013) are highly selective for the human ortholog, whereas others such as pemirolast and amlexanox are highly selective for the rat ortholog.…”
Section: Discussionmentioning
confidence: 92%
“…4B). We and others have reported that many compounds first identified as ligands at human GPR35, including zaprinast, display markedly different potency and/or activity at rodent orthologs (Taniguchi et al, 2006;Jenkins et al, 2010Jenkins et al, , 2012Funke et al, 2013;Neetoo-Isseljee et al, 2013). We next examined the activity of a variety of mast cell stabilizers at the rat ortholog of GPR35 in the BRET-based b-arrestin-2 interaction assay.…”
Section: Compoundmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, despite both kynurenic acid (Wang et al, 2006) and lysophosphatidic acid (Oka et al, 2010) being proposed as endogenous activators of GPR35, the synthetic ligand zaprinast has become the standard reference agonist. Zaprinast, however, is better appreciated as an inhibitor of cGMP phosphodiesterases (Taniguchi et al, 2006), and other recently reported GPR35 agonists are generally either very simple molecules with modest potency/ affinity and known activity at multiple other targets (Yang et al, 2010(Yang et al, , 2012Hu et al, 2012) or were identified via screens of libraries of known therapeutic ligands (Jenkins et al, 2010). As such, the identification of pamoate as a relatively potent GPR35 agonist (Jenkins et al, 2010;Zhao et al, 2010) potentially offers a more useful tool.…”
Section: Discussionmentioning
confidence: 99%